Effects of synthetic explanatory variable on saturation magnetization of colloidal nanomagnetite slurry - Bagheri, S.; Ramimoghadam, D.; TermehYousefi, A.; Abd Hamid, S.B. (Elsevier, 2015)
In this contribution, stable nanomagnetite slurry have been successfully prepared by coprecipitation method. The synthesis parameters, such as reaction temperature, heating time, surfactant concentration and precipitating agent addition rate affected magnetic properties of synthetic nanomagnetite slurries were also investigated. We discovered the optimum reaction parameters based on the highest saturation magnetization obtained under our experimental condition to disperse magnetite nanoparticles in the aqueous medium using dodecanoic acid as a surfactant. The highest saturation magnetization was achieved when 0.5:1 mole ratio of dodecanoic acid to magnetite was used and NH4OH with an addition rate of 5 ml min(-1) was added to the solution while time and temperature for heating were 45 min at 80 degrees C. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.